Modern Opportunities For Ecotourism Development In Uzbekistan - Djurakulov Khusan Anvarovich (Periodica Journal, 2025)
This article presents research and scientific conclusions on the possibilities of developing ecotourism in our country, based on its unique characteristics, such as its natural flora and fauna, mountainous and foothill areas, clean air, and water resources.
Keywords: environment; tourism; ecotourism